Analysis of Students' Creative Thinking in Solving Pythagorean Theorem Problems - Surya Bakti Pandiangan; Firman Pangaribuan; Gayus Simarmata (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The purpose of this study is to analyze the Creative Thinking Ability at UPTD SMP Negeri 12 Pematangsiantar Academic Year 2023/2024 located at Jl. Sibolga No. 12, Karo, Kec. South Siantar, Pematangsiantar City, North Sumatra Province. The subjects in this study were students who could be a source of information regarding the problems to be studied, so that the research subjects in the study entitled Analysis of Students' Creative Thinking in Solving Pythagorean Theorem Problems were 30 students in grades IX-7. Based on the results and discussions that the researcher has presented, the researcher can draw the following conclusions: 1. In Fluency Thinking, students with high, medium and low Creative Thinking abilities can gather information to form ideas. Subjects with high, medium, and low Creative Thinking abilities gain knowledge from learning experiences in the classroom. 2. At the Flexible Thinking stage, students who have high, medium, and low Creative Thinking abilities look for formulas according to the known questions. The higher the level of student creativity, the more diverse the answer solutions that emerge. While students who have low Creative Thinking skills cannot come up with diverse answers. 3. At the Originality stage, students who have high and moderate Creative Thinking skills are productive in producing unique answers, while subjects with low Creative Thinking skills are not productive in providing answers. Students who have low Creative Thinking skills give random answers because they do not have other alternative ways. 4. At the elaboration skill stage, students who have high and moderate Creative Thinking skills are able to develop detailed ideas often with innovative solutions while subjects with low Creative Thinking skills tend to provide a limited idea development process, with ideas that are less in-depth and less detailed in developing solutions.